Is VO2 kinetics influenced by swimming intensity in maximal and supramaximal velocities in young female swimmers? - Almeida, T.; Filho, D. M. P.; Espada, M.; Reis, J.; Simionato, A.; Siqueira, L.; Sancassani, A.; Oliveira, J.; Alves, F. (Journal of Human Sport & Exercise, 2019)
The aim of the present study was to determine if VO2 Kinetics (VO2K) and specifically, the time constant (ƒä) from rest to maximal and supramaximal velocities is influenced by the swimming intensity. Thirteen well trained female swimmers performed a discontinuous incremental test for maximal oxygen uptake (VO2peak) and maximal aerobic velocity (MAV) assessment and, two 100-m transitions for MAV (100MAV) and all out sprint (100MT). In the 100-m tests, maximal rise of VO2 (VO2rise), oxygen deficit at the onset of exercise (O2InitialDef) and VO2K were determined. All tests were conducted using a breath-by-breath apparatus (K4b2, Cosmed, Italy) connected to a swimming snorkel (new-AquaTrainerR, Cosmed, Italy) for pulmonary gas sampling and an underwater visual pacer for velocity control. VO2peak at the incremental test was significantly higher than the VO2rise of both 100-m tests. Swimmers presented a significantly faster VO2K response (lower ƒä) at the 100MT (~12s Vs ~26s) which lead to a significantly lower O2InitialDef compared to the 100MAV. VO2rise and ƒä were correlated between tests (r=0.71, p<0.01 and r=0.59, p<0.05, respectively). Based on our results it seems that the VO2K is influenced by the exercise intensity at maximal and supramaximal intensities, getting faster as the exercise becomes more demanding. Furthermore, the capacity of attaining higher oxidative rates could be related to the physiological characteristics of the swimmers, since those who were more efficient in a physiological point of view (faster kinetics with higher VO2) in one test were those who presented better results in the other.